2002
DOI: 10.1046/j.1365-2958.2002.03165.x
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity in Saccharomyces cerevisiae is modulated by calcium signalling

Abstract: SummaryThe most important group of antifungals is the azoles (e.g. miconazole), which act by inhibiting lanosterol demethylase in the sterol biosynthesis pathway. Azole activity can be modulated through structural changes in lanosterol demethylase, altered expression of its gene ERG11 , alterations in other sterol biosynthesis enzymes or altered expression of multidrug transporters. We present evidence that azole activity versus Saccharomyces cerevisiae is also modulated by Ca 2 + + + + -regulated signalling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
86
2
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(95 citation statements)
references
References 47 publications
5
86
2
2
Order By: Relevance
“…Trp was shown to mitigate the antifungal activity of ibuprofen, an anti-inflammatory agent with antifungal action, and of the calcineurin inhibitor FK506, an immunosuppressant with antifungal activity (16,18). Interestingly, we also found the calcineurin cnb1 deletion mutant to be hypersensitive to miconazole, as was previously demonstrated by Edlind et al (19). However, it is not clear how Trp can protect yeast cells against various stresses.…”
Section: Discussionsupporting
confidence: 78%
“…Trp was shown to mitigate the antifungal activity of ibuprofen, an anti-inflammatory agent with antifungal action, and of the calcineurin inhibitor FK506, an immunosuppressant with antifungal activity (16,18). Interestingly, we also found the calcineurin cnb1 deletion mutant to be hypersensitive to miconazole, as was previously demonstrated by Edlind et al (19). However, it is not clear how Trp can protect yeast cells against various stresses.…”
Section: Discussionsupporting
confidence: 78%
“…We verified this idea as we showed that activation of FKS2, a well established reporter gene of cell wall defects (6,17,29), in response to Calcofluor White or in a gas1 mutant was reduced upon the removal of the CDRE element present in the promoter of this gene. Interestingly, two recent papers reported the implication of calcium signaling in the tolerance of yeast to antifungal azoles (96) and in transcriptional induction of genes in response to alkaline pH (97). Altogether, these data demonstrate a major contribution of the calcium signaling in adaptation of yeast cells to various stresses.…”
Section: Discussionmentioning
confidence: 67%
“…Relatedly, the signaling pathways that mediate phenotypic adaptation to antifungal treatment are just beginning to be understood. Recent studies have implicated the calcium-calmodulin-calcineurin (7,11,24,26) and protein kinase C (PKC)-cell integrity (T. D. Edlind, Abstr. 41st Intersci.…”
mentioning
confidence: 99%